Growth Response And Results Of Local Upland Rice Cultivars West Sumatera On Ultisol Land - Ediwirman ediwirman (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Upland rice whose cultivated on dry land, which has limited needs for growth and production. The low upland rice production is due to the lack of high yielding varieties that can adapt, especially to marginal lands such as Ultisol. There are quite many local upland rice lines, but their potential has not been tested much. This study aimed to obtain the growth and yield of local upland rice cultivars of West Sumatra on the best Ultisol soil. The study used a completely randomized design (CRD) with four replications. The treatments were four upland rice cultivars, which consisted of; Silayang (K1), Siarang (K2), Sirah (K3) and Sigudang (K4). This data observation was analyzed for variance, and if it had a significant effect, it was continued using DMRT at the 5% level. Observations were made on plant height, the maximum number of tillers, percentage of productive tillers, length of flag leaf, age of flowering, age of the first harvest, panicle length, number of grain per panicle, the weight of 1000 pithy grain seeds, and weight of pithy grain per clump. Based on the results of the study, it was concluded that upland rice cultivar Sirah had the best growth and yield on Ultisol soil. Based on the conclusion, it is recommended to use Sirah upland rice on Ultisol soil.